2008
DOI: 10.1016/j.tripleo.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal changes in the condylar head after sagittal split ramus osteotomy with bent plate fixation

Abstract: Results. There was no significant difference in reduction in mandibular length between SSRO alone and SSRO with Le Fort I on the axial view of a 3D CT. There were no significant differences between pre-and postoperative horizontal changes in the condylar long axis or in the antero-posterior and medio-lateral displacement of the condylar head, although the length of the proximal segment in SSRO with Le Fort I osteotomy was significantly shorter than in SSRO alone (P<0.05). Conclusion.These results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 19 publications
(20 reference statements)
1
26
0
Order By: Relevance
“…9 In our previous study using CT, we also did not observe significant changes in condylar position or angle, but the gap between the proximal and distal segment created by the bent plate might reduce stress on the TMJ. 10 It is unclear whether bone healing could complete without bony contact between the proximal and distal segments. For fracture surgery, Perren and other members of the ASIF/AO School 11,12 state that compression of the fragments is essential to primary bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…9 In our previous study using CT, we also did not observe significant changes in condylar position or angle, but the gap between the proximal and distal segment created by the bent plate might reduce stress on the TMJ. 10 It is unclear whether bone healing could complete without bony contact between the proximal and distal segments. For fracture surgery, Perren and other members of the ASIF/AO School 11,12 state that compression of the fragments is essential to primary bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Although many methods 7,8,[21][22][23] to prevent condylar displacement have been reported, few studies are available regarding the factors influencing condylar displacement after SSRO. Harris et al 6 and Lee and Park 9 evaluated condylar displacement by SSRO in three dimensions by means of helical CT and correlated with the amount of mandibular advancement 6 or setback.…”
Section: Discussionmentioning
confidence: 99%
“…Although the changes in condyle position were obvious, influencing factors were not revealed in their study. Ueki et al 7,8 reported that condylar rotation after SSRO could be reduced considerably with the use of bent plates. They also demonstrated that the frequency of temporomandibular disorders after surgery in the bent-plate group was significantly less than that in the conventional straight-plate group.…”
Section: Introductionmentioning
confidence: 99%
“…This postoperative increase in ramus might partially depend on our surgical method reported previously. 21 In this method, the gap between the proximal and distal segment is created by a bent plate, preventing formation of a large bony contact.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the gap was created between the osteotomy surfaces on both sides ( Fig.1). 21 Mean setback amount was right 6.2±3.0mm and left 6.6±3.2mm.…”
Section: Surgerymentioning
confidence: 91%